Population dynamics of whiskered velvet Shrimp (Metapenaeopsis barbata) in Samboja Waters, Kuala Kutai Kartanegara Regency - Alvian Rivaldy Tuppang; Muhammad Syahrir Ramang; Abdunnur Abdunnur (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Samboja Kuala has a very wide sea and has a very abundant ecosystem and natural resources. The most dominant community work in Samboja Kuala is fishermen, the fishermen's catches include fish, shrimp, seaweed, and others. Brown Spot Shrimp (Metapenaeopsis barbata) is one of the catches in Samboja Kuala waters. Brown spot shrimp catches operate during the day as well as at night. This study was conducted in November-December 2022. Sampling using trawl fishing gear. The purpose of this study was to calculate sex ratio, age estimation, age group, mortality, and growth pattern. The sex ratio has 200 males and 300 shrimp females have a ratio of 0.66: 1.50. Age estimation of males and females, with growth rate (K) of male brown spot shrimp of 1,400 and females of 1.1 00, while asymbiotic length value (L∞) in males of 95.90 and females of 94.44. The age group of males ranges from 48.2 7 mm – 87.32 mm , females range from 47.2 2 mm – 84.45 mm,. The total coefficient mortality (Z) of males and females was 3.25 per year and 2.79 per year. The natural mortality coefficient (M) of males and females was 1.63370 per year and 1.40121 per year. The mortality coefficient due to capture of (F) males and females was 1.62 per year and 1.39 per year. The male and female utilization rates are 0.50 and 0.50. On the growth pattern has the results of the analysis of males, a new addition occurred in June amounting to 28.6.5,%. in females a new addition occurred in July of 15.05,%.